Insights on a rare species, 'Geum atlanticum', new data to differentiate from 'Geum sylvaticum' - Pedro Sánchez-Gómez; Jose Luis Cánovas; Juan F. Jiménez (Mediterranean Botany, 2021)
Geum atlanticum is a species described from North Africa and later found in Southern Iberian Peninsula. However, according to Flora iberica taxonomic treatment, it has been considered synonymous with G. sylvaticum, a species mainly distributed by Southeast of France, Iberian Peninsula, and North of Africa, sharing part of the distribution range and habitat. In this work, herbarium specimens of both G. atlanticum and G. sylvaticum were revised to evaluate morphological differences. Furthermore, the nuclear ribosomal ITS spacer was sequenced to study phylogenetic relationships among G. atlanticum and Iberian Geum species. The morphological study indicated clear differences with G. sylvaticum, and the phylogenetic analysis suggests that G. atlanticum was sister to G. sylvaticum. However, it shared several mutations with other Iberian Geum species. The number of populations is relatively low in the Iberian Peninsula, so its conservation status and its further inclusion in lists of threatened plants have been evaluated in this work.